Governance and sustainability in brazilian electricity companies: Corporate governance, social responsibility, Energy. - Oliveira, Isaac Gezer Silva de (Revista de Negócios, 2024)
The current economic context calls for socio-environmental responsibility and corporate governance policies in order to align the interests among the different social participants in great corporations. Therefore, and based on the hypothesis that the creation of corporate value is positively associated with good governance and entrepreneurial sustainability practices, this study seeks to analyze the relationship between performance and governance and social responsibility in light of the Agency Theory and the Stakeholders Theory. The investigation was carried out in companies listed in the São Paulo Stock Exchange for the electric energy which consists of a sector of high environmental and social impact. For the data analysis linear regression models with panel data by Random Effects and by Generalized Systemic Moments method (GMM-Sys) were used. The results of the investigation suggest that companies with adequate governance and social responsibility practices have a higher market value. It can be concluded that said practices, besides meeting ethical, legal and society precepts, contribute to the creation of corporate value.